PERAN GURU TERHADAP SIKAP TOLERANSI BERAGAMA PADA ANAK USIA DINI DI TK PERTIWI METRO PUSAT - Vani, Yulis Okta; Noormawanti, Noormawanti; Firdausyi, Annisa Nur (Thufulah: Jurnal Ilmiah Mahasiswa, 2024)
Diverse nation, with various religions and beliefs. Early childhood education covers 6 aspects of development that are very important in shaping a child's personality, including an understanding of religious tolerance. At Pertiwi Metro Kindergarten, which has students from various religious backgrounds, teachers play a key role in educating, directing and instilling the values ​​of tolerance, The research method used is a qualitative approach with a descriptive type. Sources of research data include Pertiwi Metro Pusat Kindergarten teachers. Data collection techniques are interviews and documentation and observation. The data analysis techniques used are data condensation, data presentation and conclusion drawing. Test the validity of the data using triangulation of sources, techniques and time.The research results show that teachers at Pertiwi Metro Kindergarten play an important role in instilling the values ​​of religious tolerance in early childhood. They develop a curriculum that emphasizes the values ​​of tolerance through stories, songs and routine class activities, as well as being role models in everyday behavior. An inclusive learning environment is created so that every child feels accepted regardless of religious background, and communication with parents is established to strengthen the understanding of tolerance at home. This school integrates religious activities according to each child's beliefs and regularly evaluates the tolerance program through observation and feedback from parents. Despite the challenges of diversity in family backgrounds, schools overcome them with training for teachers and dialogue with parents. As a result, children at Pertiwi Metro Kindergarten show a better understanding of religious differences and mutual respect, forming the basis for a harmonious society in the future. This research also highlights the importance of collaboration between teachers and parents, as well as an integrated learning approach that includes activities for Muslim and non-Muslim children, in creating an inclusive environment that respects religious diversity